2018
DOI: 10.1136/bmjopen-2017-020497
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis recognition tools in acute ambulatory care: associations with process of care and clinical outcomes in a service evaluation of an Emergency Multidisciplinary Unit in Oxfordshire

Abstract: ObjectiveTo assess the performance of currently available sepsis recognition tools in patients referred to a community-based acute ambulatory care unit.DesignService evaluation of consecutive patients over a 4-month period.SettingCommunity-based acute ambulatory care unit.Data collection and outcome measuresObservations, blood results and outcome data were analysed from patients with a suspected infection. Clinical features at first assessment were used to populate sepsis recognition tools including: systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
11
1
6
Order By: Relevance
“…To our knowledge, this is one of the few studies on the novel Sepsis-3 criteria specifically focused on geriatric multimorbid patients, and the first one performed in an acute-care geriatric ward. In fact, previous studies enrolling only subjects aged 70 or older were performed in emergency departments [36,37] or primary care [38]. The results of these studies are apparently in conflict with our findings, since they showed a good prognostic performance by qSOFA for short-term mortality in emergency departments [36,37] and a better prognostic performance by SIRS in primary care [38].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, this is one of the few studies on the novel Sepsis-3 criteria specifically focused on geriatric multimorbid patients, and the first one performed in an acute-care geriatric ward. In fact, previous studies enrolling only subjects aged 70 or older were performed in emergency departments [36,37] or primary care [38]. The results of these studies are apparently in conflict with our findings, since they showed a good prognostic performance by qSOFA for short-term mortality in emergency departments [36,37] and a better prognostic performance by SIRS in primary care [38].…”
Section: Discussioncontrasting
confidence: 97%
“…In fact, previous studies enrolling only subjects aged 70 or older were performed in emergency departments [36,37] or primary care [38]. The results of these studies are apparently in conflict with our findings, since they showed a good prognostic performance by qSOFA for short-term mortality in emergency departments [36,37] and a better prognostic performance by SIRS in primary care [38]. However, recent literature supports the concept that the predictive capacity of qSOFA and SIRS may differ, according to the characteristics of patients and healthcare settings [10,20], and this consideration also applies to older patients, who are admitted to non-ICU wards.…”
Section: Discussionmentioning
confidence: 99%
“…These studies recruited a total of 107,008 participants, and the mortality rate in each study ranged from 2.5 to 32.8%. Five studies (20,24,27,31,32) were relatively small in sample size (<400), and 10 studies (19, 23, 26, 28-30, 33, 36, 37, 40) enrolled more than 1,000 patients. Ten studies (19,21,22,(27)(28)(29)(32)(33)(34)(35) included patients with suspected infection, and others focused on patients with suspected sepsis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Kondisi trauma organ dan kerusakan permukaan tubuh yang luas menyebabkan pasien dengan cedera ledakan rentan mengalami sepsis. Sepsis merupakan kondisi disfungsi organ yang mengancam jiwa yang disebabkan oleh disregulasi respon tubuh terhadap infeksi (Camm et al, 2018;Finkelsztein et al, 2017).…”
Section: Pendahuluanunclassified